2006
DOI: 10.1152/ajprenal.00405.2005
|View full text |Cite
|
Sign up to set email alerts
|

AT1receptor-mediated accumulation of extracellular angiotensin II in proximal tubule cells: role of cytoskeleton microtubules and tyrosine phosphatases

Abstract: Long-term angiotensin II (ANG II) administration is associated with increased ANG II accumulation in the kidney, but intrarenal compartment(s) involved in this response remains to be determined. We tested the hypothesis that 1) extracellular ANG II is taken up by proximal tubule cells (PTCs) through AT(1) receptor-mediated endocytosis, 2) this process is regulated by cytoskeleton microtubule- and tyrosine phosphatase-dependent mechanisms, and 3) AT(1) receptor-mediated endocytosis of ANG II has a functional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(125 citation statements)
references
References 43 publications
13
112
0
Order By: Relevance
“…36 Ang II has also been shown to stimulate AT 1a -receptor internalisation 95,96 we showed that intracellular Ang II levels were increased more than two-fold when they were incubated with exogenous Ang II, and this response was inhibited by the ARB losartan and the cytoskeleton microtubule inhibitor colchicine or the tyrosine phosphatase inhibitor phenylarsine oxide (PAO). 46 These results support the concept that proximal tubule cells take up extracellular Ang II via AT 1 -receptor-mediated endocytosis and the process requires interactions with cytoskeleton microtubules and tyrosine phosphatases.…”
Section: At 1 -Receptor-mediated Accumulation Of Extracellular Ang IIsupporting
confidence: 81%
See 1 more Smart Citation
“…36 Ang II has also been shown to stimulate AT 1a -receptor internalisation 95,96 we showed that intracellular Ang II levels were increased more than two-fold when they were incubated with exogenous Ang II, and this response was inhibited by the ARB losartan and the cytoskeleton microtubule inhibitor colchicine or the tyrosine phosphatase inhibitor phenylarsine oxide (PAO). 46 These results support the concept that proximal tubule cells take up extracellular Ang II via AT 1 -receptor-mediated endocytosis and the process requires interactions with cytoskeleton microtubules and tyrosine phosphatases.…”
Section: At 1 -Receptor-mediated Accumulation Of Extracellular Ang IIsupporting
confidence: 81%
“…[42][43][44] Whether internalised or intracellular Ang II plays a physiological and/or pathological role in proximal tubule cells remains to be further studied. 45,46 Since proximal tubule cells reabsorb more than 65-70% of glomerular filtered sodium load, and increased sodium reabsorption in this nephron segment by extracellular and intracellular Ang II will promote sodium and fluid retention and consequently the development of hypertension. Acting as a powerful intracellular cytokine and growth factor, intracellular Ang II may also play an important role in the pathogenesis of Ang IIinduced hypertensive renal injury, especially tubulo-interstitial fibrosis.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
“…This is a major drawback of this compound, as we now know that nonphagocytic NAD(P)H oxidase is active in the cytosol itself. Some studies have found utility for this compound in modulating Ang II signaling through its anti-tyrosine phosphatase activity (138,186). Tyrosine phosphatases play an important role in the internalization of AT 1 R and Ang II into PTCs (186).…”
Section: Role Of Renal Oxidative Stress In Hypertension 2073mentioning
confidence: 99%
“…Some studies have found utility for this compound in modulating Ang II signaling through its anti-tyrosine phosphatase activity (138,186). Tyrosine phosphatases play an important role in the internalization of AT 1 R and Ang II into PTCs (186). Others have demonstrated activation of eNOS, leading to improvement in endothelial dysfunction (68).…”
Section: Role Of Renal Oxidative Stress In Hypertension 2073mentioning
confidence: 99%
“…The canonical clathrin-dependent endocytosis pathway for Ang Ⅱ occurs in different cell types, such as vascular smooth muscle and human embryonic kidney (HEK-293) cells through the AT1 receptor, c-Src and clathrin Adapter Protein 2 [112] . In rabbit proximal tubule cells, the alternative microtubule-associated endocytic pathway rather than the clathrin-dependent pathway participates in the AT1 receptor-mediated uptake of Ang Ⅱ [113] . Another alternative endocytic pathway for Ang Ⅱ internalization in proximal tubule cells has been described by Gonzalez-Villalobos et al [114] , where anti-megalin antisera interferes with Ang Ⅱ binding in cell brush-border membrane vesicles extracted from mice, indicating that Ang Ⅱ internalization is a megalin-dependent process.…”
Section: Breaking Paradigmsmentioning
confidence: 99%